Case Report, Practices Survey and Literature Review of an Under-Recognized Pediatric Vascular Disorder: The BASCULE Syndrome - Baurens, Natacha; Briand, Clémence; Giovannini-Chami, Lisa; De Guillebon De Resnes, Jean-Marie; Hubiche, Thomas; Chiaverini, Christine; Giordana, Pascal; Leftheriotis, Georges; Bernardor, Julie (Frontiers in Pediatrics, 2022)
Introduction Bier anemic spots, cyanosis, and urticaria-like eruption (BASCULE) syndrome is an underreported pediatric vascular disorder from the group of acrosyndromes. In children, these include paroxysmal acrosyndromes (Raynaud’s phenomenon and chilblain-like lesions), permanent acrosyndromes (acrocyanosis), and transient acrosyndromes, in which their pathogeneses are associated with virus infections, Epstein-Barr virus, and, more recently, SARS-CoV-2, respectively. Methods We reported a case of BASCULE syndrome associated with postural orthostatic tachycardia syndrome (POTS) and provided a narrative review of case reports describing the BASCULE syndrome in children. Moreover, we presented the results of a prospective practice survey that we performed in the French medical community. Results A 14-years-old boy reported pruritic erythrocyanic lesions on the lower limbs, which occurred whenever he was in a standing position and fully resolved when he laid down. He reported asthenia and cramps. He presented a typical BASCULE syndrome associated with POTS confirmed by a tilt-test. Physical and vascular examinations were within the normal range. We identified 12 case reports, describing 21 pediatric cases since 2016. Most patients were adolescents between 12 and 19 years of age or were newborns. Furthermore, 20% of cases in the literature have presented POTS or orthostatic intolerance. Our survey among 95 French physicians confirmed that BASCULE syndrome is an underdiagnosed and under recognized disease in the general pediatric practice, at least in France. Among these physicians, 65% had already encountered patients with similar symptoms, but only 30% declared that they had knowledge of the BASCULE syndrome. Conclusion The under-recognition of the clinical manifestations leads the patients to consult emergency rooms, with multiple unnecessary investigations performed. Therefore, we suggest that the diagnosis of BASCULE syndrome is based on clinical observations, without the need for laboratory tests, to avoid unnecessary health costs. We suggest physicians to perform a tilt-test when POTS is suspected.